PENERAPAN METODE CERTAINTY FACTOR DALAM MENENTUKAN MAKANAN YANG DIKONSUMSI BERDASARKAN KONDISI DAN KEBUTUHAN STANDAR TUBUH MANUSIA - Abdul Haris (Sekolah Tinggi Teknik - PLN, 2015)
It has been long to known that food plays an important role in efforts to prevent and curediseases, to develop the human resources potential, achieve a better quality and achieve longer lifeas well. It is proper nutrition issues into the affairs of all of us, both at the individual, household, andnational levels.In a healthy or unhealthy condition, food needs to be regulated well. Because of shortage andexcess nutrients will cause the body disease. This occurs because of an error in dietary habit and alack of understanding and knowledge of proper nutrition. This is the reason that author wants tomake an application on nutrition with method certainty factor. So users have a better knowledgeabout nutrition. Desktop application created with Visual Basic .NET using Oracle Database.